Unraveling institutional complexity in engaged education practices: rationales, responses, and roles of individual practitioners - Tijsma, Geertje; Demeijer, Frederique; Zweekhorst, Marjolein; Urias, Eduardo (Frontiers in Education, 2024)
Despite the growing trend to integrate engaged education activities in (Higher) Education Institutions ((H)EIs), their adoption responds to diverse and often conflicting rationales. These rationales are shaped by institutional logics at both the field and organizational level, and their conflicting nature is a manifestation of the institutional complexity that arises when organizations and the individuals within them are confronted with divergent prescriptions from multiple institutional logics. This study examines how engaged practitioners in (H)EIs experience institutional complexity and how they respond to such complexities. We conducted research at the intersection of field-level and organizational-level logics, and individual responses. Our findings show that engaged practitioners who initiate engaged education that follows the principles of the dominant market and corporate logics do not experience institutional complexity, and we therefore refer to them as compliers. Conversely, those whose intentionality follow the minority state logic take different roles in their response to the underlying institutional complexity. Those roles may refer to the adherence to multiple conflicting logics while keeping them apart (compartmentalizers), the (selective) combination of elements of dominant and minority logics (combiners), or the (partial) rejection of the dominant logic to protect the minority logic (protectors). The implications of our study offer valuable insights into the change process in (H)EIs concerning the integration of engaged educational processes and activities.